Regulation of vascular smooth muscle cell calcification by extracellular pyrophosphate homeostasis: synergistic modulation by cyclic AMP and hyperphosphatemia - Prosdocimo, Domenick A. (American Physiological Society, 2010)
Vascular calcification is a multifaceted process involving gain of calcification inducers and loss of calcification inhibitors. One such inhibitor is inorganic pyrophosphate (PP(i)), and regulated generation and homeostasis of extracellular PP(i) is a critical determinant of soft-tissue mineralization. We recently described an autocrine mechanism of extracellular PP(i) generation in cultured rat aortic vascular smooth muscle cells (VSMC) that involves both ATP release coupled to the ectophosphodiesterase/pyrophosphatase ENPP1 and efflux of intracellular PP(i) mediated or regulated by the plasma membrane protein ANK. We now report that increased cAMP signaling and elevated extracellular inorganic phosphate (P(i)) act synergistically to induce calcification of these VSMC that is correlated with progressive reduction in ability to accumulate extracellular PP(i). Attenuated PP(i) accumulation was mediated in part by cAMP-dependent decrease in ANK expression coordinated with cAMP-dependent increase in expression of TNAP, the tissue nonselective alkaline phosphatase that degrades PP(i). Stimulation of cAMP signaling did not alter ATP release or ENPP1 expression, and the cAMP-induced changes in ANK and TNAP expression were not sufficient to induce calcification. Elevated extracellular P(i) alone elicited only minor calcification and no significant changes in ANK, TNAP, or ENPP1. In contrast, combined with a cAMP stimulus, elevated P(i) induced decreases in the ATP release pathway(s) that supports ENPP1 activity; this resulted in markedly reduced rates of PP(i) accumulation that facilitated robust calcification. Calcified VSMC were characterized by maintained expression of multiple SMC differentiation marker proteins including smooth muscle (SM) α-actin, SM22α, and calponin. Notably, addition of exogenous ATP (or PP(i) per se) rescued cAMP + phosphate-treated VSMC cultures from progression to the calcified state. These observations support a model in which extracellular PP(i) generation mediated by both ANK- and ATP release-dependent mechanisms serves as a critical regulator of VSMC calcification.